The impact of emotional intelligence on work performance among ICU nurses in Palestine: a cross-sectional study - Imad H. Fashafsheh; Faeda A. Eqtait; Bahaaeddin M. Hammad; Ahmad J. Ayed; Basma S. Salameh (BMC Nursing)
Abstract Background Emotional intelligence plays a crucial role in work performance, especially in high-stress ICU settings. Understanding emotional intelligence’s role can inform targeted interventions to support nurse well-being, enhance resilience, and improve patient outcomes. Methods This descriptive cross-sectional study involved 226 ICU nurses in Palestine, recruited through a convenience sampling method. Data were collected using self-administered questionnaires, including the Schutte Emotional Intelligence Test and a job performance scale. Descriptive statistics, correlation analyses, and regression models were used to analyze predictors of job performance. Results The study included 226 nurses, mostly male (74.3%), aged 21–30 years (71.2%), with a bachelor’s degree (68.1%) and less than five years of ICU experience (59.3%). Emotional intelligence scores were high, with an average of 151.9 ± 1.9, and perception of emotions had the highest subscale score. Work performance was also high, averaging 4.3 ± 0.7, with job quality and job quantity scoring the highest. A strong positive correlation (r = 0.611, P < 0.05) was found between EI and work performance. EI and educational level were significant predictors of work performance (β = 0.123, p < 0.01), explaining 39.3% of the variance. Conclusion the study highlights the critical role of emotional intelligence in improving ICU nurses’ work performance, particularly in job quality and quantity. Higher emotional intelligence helps nurses meet ICU demands, while educational level serves as a key predictor of performance. These findings highlight the need for EI training in nursing education, professional development, and workplace policies. Structured programs can enhance nurses’ decision-making, communication, and stress management, ultimately improving performance, patient care quality, and safety. Future research should adopt longitudinal or experimental designs to establish causality and evaluate the impact of EI training on nursing performance. Clinical trial number Not applicable.